Implementasi Manpower Planning Approach untuk Optimalisasi Kompetensi Lulusan Jurusan Perhotelan di SMK Mutiara Terpadu Palabuhan Ratu - Hermawan, Ridwan; Qomariyah, Siti; Alfauzi, Hasbulloh Karim; Muslimat, Emat; Hadad, Nawil (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
The Manpower Planning Approach plays a strategic role in enhancing the quality of vocational education and producing graduates who are competent and job-ready in the hospitality sector. This approach is crucial in bridging the gap between graduates’ competencies and the needs of the service industry, which demands high professionalism, excellent service skills, and a strong work ethic. This study aims to comprehensively examine the implementation of the Manpower Planning Approach in the Hospitality Department, covering aspects such as planning, strategy, challenges, solutions, and evaluation. The research employs a qualitative approach, utilizing data collection techniques including classroom observations, interviews with teachers and students, and analysis of learning documents. The findings indicate that the implementation of the Manpower Planning Approach in the Hospitality Department has been carried out systematically and is oriented toward industry needs. The school applies a competency-based curriculum, enhances teacher capacity through industrial training, and strengthens partnerships with hotel industries for internship programs. Although several challenges remain such as limited practical facilities, a shortage of productive teachers, and rapid changes in the hospitality industry continuous improvement efforts have been made through strengthening partnerships, improving teacher competence, and developing learning facilities. This approach has proven effective in increasing the relevance of vocational education and enhancing the competitiveness of graduates in the hospitality sector.